Summer range fidelity of radio-collared caribou in Alaska's Central Arctic Herd - Cameron, R.D.; Whitten, K.R.; Smith, W.T. (Rangifer, 1986)
Sixty-four adult (2 + years) female caribou (Rangifer tarandus grand), radio-collared in April or May 1975 - 82, were relocated during the following June and/or July within the summer range of the Central Arctic Herd (CAH). Relocations made during the following three summers were used to assess range fidelity. Cumulative relocations of radio-collared females in the Central Arctic region were equivalent to 91% of the projected availability based on transmitter life. A chronological analysis indicates that 98%, 91%, and 82% of radio-collared females were found there one, two, and three years later; most of the progressively lower relocation success is probably attributable to transitter malfunctions rather than emigration. These observations suggest that summer range fidelity of adult females in the CAH is at least 90%, and may approach 100%.